Should jual janji transaction be recognised by the courts? / Mohd Norzaki Mohd Yusop …[et al.] - Mohd Yusop, Mohd Norzaki; Salehudin, MuhamadShah Fareez; Hood, Muhammad Hafiz; Ikhsan, Muhammad Izwan (2009)
The quandary that encircles the practice of jual janji in Peninsular Malaysia is no alien to the legal scholars, judges, lawyers and students. The utmost dilemma that surrounds jual janji is on its undetermined status as a security transaction. Thus, this paper will attempt to convert the assorted problems encountered by jual janji transaction into a vibrant future by proposing certain viable and realistic strides in effort of revitalizing the subsistence of jual janji transaction and deciphering the difficulty concerning its legitimacy. In doing so, the historical outlines of jual janji transaction prior and after the passing of the National Land Code 1965 (NLC) will be scrutinized, the reasons for inferiority of jual janji will be examined and the conflicting court's interpretation in responding to the issue of recognition of jual janji will be appraised and compared. Finally, this paper will also enclose the conclusions and the promising recommendations in response to the research questions.